PENGARUH PENGGUNAAN VIDEO ANIMASI PEMBELAJARAN TERHADAP HASIL BELAJAR SISWA SEKOLAH DASAR KELAS V SDN KOTABUMI CILEGON - Dandy Rizky Oktariansyah; Beni Junedi, Ade Fricticarani (STKIP Subang, 2025)
This study aims to examine the effect of animated learning videos on the learning outcomes of fifth-grade students at SDN Kotabumi, Cilegon. Unsatisfactory learning outcomes, particularly in subjects requiring complex concept understanding, prompted this research. A quasi-experimental design was employed, involving 50 students divided into experimental (using animated videos) and control (conventional methods) groups. Data were collected through pre-tests and post-tests, analyzed using descriptive statistics, normality tests (Kolmogorov-Smirnov and Shapiro-Wilk), homogeneity tests (Levene’s Test), independent t-tests, and N-gain analysis. Results showed a significant difference between groups (t = -4.542, p < 0.001), with a mean difference of -4.040 (95% CI: -5.829 to -2.251). The N-gain analysis indicated a greater improvement in the experimental group (M = 36.385, SD = 4.221) compared to the control group (M = 10.801, SD = 4.526). These findings confirm that animated videos effectively enhance student learning outcomes. Recommendations include teacher training in technology integration and further research on combining instructional media.